Strategies to Increase Customer Interest by Implementing Digital Marketing at Hello Friends Coffee Shop in South Jakarta - Setiawan, Elfa; Frara, Elizabeth Monica (Eligible : Journal of Social Sciences, 2023)
This research was conducted to discover the development of customer interest through social media and find solutions to the obstacles faced. The focus of this research is related to the emergence of a "new culture" originating from an outside culture with a background in cafes or coffee shops and then influencing people's lifestyle which results in the emergence of many coffee shops. This creates competitions which requires these coffee shops to have a good marketing strategy correctly and effectively to increase customer interest. The data was collected from observation and conducting interviews with informants. Based on the results, it is concluded that the strategy of attracting customers through digital marketing has been going well. Digital marketing using social media and other media that are still included in digital marketing can also make it easier for customers and prospective customers interested in using or buying business products. It is also essential to find out the potential information customers need.